Internal Control and Risk Management in Ensuring Good University Governance - Yudianti, Fr. Ninik (Journal of Education and Vocational Research, 2015)
Human resources development has been a crucial issue in the emerging economies of Indonesia. The growth of Universities and other form of Higher Education in Indonesia indicates the raise of public and government awareness of educational quality. This awareness must be followed by higher education management ability for designing strategies and implementing them to produce high quality graduates. This study is expected to have contribution to enhance the management quality of Private Higher Education. This research aims to evaluate the implementation of Internal Control and Risk Management in ensuring Good University Governance. The data were collected from leaders of all Private Higher Education located at Special Province of Yogyakarta, the destination for most prospective students who will pursue further studies. Descriptive qualitative and regression analysis were performed to analyze the data. Research finding revealed that most of Private Higher Education had sufficient information and knowledge in implementing Internal Control, Risk Management, and Good University Governance. Other result showed that Internal Control and Risk Management positively influenced the implementation of Good University Governance. Limitation of this study was the respondents’ comprehension of the risk management terms that were not very well understood by some of the Higher Educational Institution’s Leaders.